SPECT and MRI Evaluation of Cerebrovascular Reactivity with CO2 Inhalation—A Preliminary Study - Min-Gyu Song; Jeong-Min Shim; Young-Don Son; Yeong-Bae Lee; Chang-Ki Kang (Applied Sciences)
Assessment of cerebrovascular function is crucial for managing neurological disorders, with cerebral blood flow (CBF) measurement being key. Single photon emission computed tomography (SPECT), a traditional method, uses radiation exposure. Blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) with carbon dioxide (CO2) is a non-invasive cerebrovascular reactivity (CVR) alternative, but direct SPECT-MRI CO2 comparisons for MRI’s replacement potential are limited. This study directly compared CVR from SPECT and MRI CO2 in nine healthy participants. Delay-based MRI (tcMRI) with stimulus timing correction was analyzed alongside conventional MRI. Results showed no significant CVR differences between SPECT and tcMRI (p = 0.688) or SPECT and conventional MRI (p = 0.813), indicating comparable overall CVR. However, tcMRI significantly differed from conventional MRI (p = 0.016) and showed a greater similarity to SPECT. Regionally, the largest CVR differences were observed between tcMRI and conventional MRI, particularly in the cingulate cortex, frontal lobe, and basal ganglia. These discrepancies suggest that tcMRI may capture subtle CVR abnormalities not detected by conventional MRI. The findings support the clinical utility of CO2-MRI, especially with stimulus timing correction, as a safe, repeatable, and radiation-free alternative to SPECT. In particular, tcMRI may offer advantages for repeated CVR assessments in long-term clinical monitoring.